We Get Mail Documenting the Rhetoric of Our Academic Institutions - Hurlbert, C. Mark. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Much of what characterizes, critiques, defines and describes an educator's profession and practice occurs in the form of documents which get delivered every day to the faculty mailroom. These documents are connected to cultural processes which establish hierarchies of power, exclude individuals from decision making, and foster an illusion of the free flow of apparently vital information necessary for full participation in the community. To investigate its rhetorical ramifications, all of the mail received by two professors of English over a 2-year period was studied (normally, much of it is ignored). Generally, institutional mail fosters an institutional "docility," a term, like document, which is rooted in the verb "to teach." The sheer amount of mail obscures, perhaps deliberately, any solicited invitation to participate in decision making, thus fostering a fictive perception of an elaborate and efficient communications network. Institutional power structures are emphasized by the numerous "literacy demands" which call for certain responses. Two examples are the personnel activity form, in which faculty must account for 100% of their time, and student evaluations of faculty, which engender elaborate protocols governing the transfer of power. Finally, the language of universities' documents speaks of chains of literacy demands extending beyond the confines of the university to government and industry. In this way, such documents as mission statements and long-range plans can potentially become powerful instruments of oppression. (HB)
ERIC Note: Paper presented at the Annual Meeting of the Conference on College Composition and Communication (43rd, Cincinnati, OH, March 19-21, 1992).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Discourse; College Faculty; Discourse Modes; Faculty Workload; Higher Education; Information Networks; Organizational Communication; School Administration; Teacher Responsibility; Paperwork; Organizational Culture; Speeches/Meeting Papers